Complexity control in semantic identification. (2nd June 2006) - Falelakis, Manolis; Diou, Christos A.; Delopoulos, Anastasios
This work introduces an efficient scheme for identifying semantic entities within multimedia data sets, providing mechanisms for modelling the trade-off between the accuracy of the result and the entailed computational cost. Semantic entities are described through formal definitions based on lower-level semantic and/or syntactic features. Based on appropriate metrics, the paper presents a methodology for selecting optimal subsets of syntactic features to extract, so that satisfactory results are obtained, while complexity remains below some required limit.